URGENSI PERLINDUNGAN HUKUM ATAS LEGALITAS PERUSAHAAN FINANCIAL TECHNOLOGY YANG BERDAMPAK PENYALAHGUNAAN DATA PRIBADI - Weny Anggun Hapsari (2021)
Legal protection of the legality of financial technology companies that have an impact on the misuse of personal data is currently very necessary, given the rampant cases of abuse that spread to other legal domains. The urgency of regulations that can be a preventive step as well as fill the void in norms in Indonesia, is one of the actions that can be taken to prevent loss of personal data for consumers. This research was conducted with a conceptual approach, with primary, secondary, and tertiary legal material sources collected through literature study. The data processed through a content analysis process to be written using descriptive writing techniques.